자세 부하를 줄이기 위한 사용자 중심 농기구 디자인 연구 - 강채우; Kang Chaewoo (한국디자인포럼, 2024)
연구배경 현대 과학기술의 발전과 국가 및 공공차원의 과학영농의 실현은 농업생산성 향상과 더불어 노동력 절감을 크게 이뤄냈다. 하지만 아직도 농업인의 노령화와 비탈진 경지 등 여러 구조적 한계로 인해 다른 어떤 산업분야보다도 농업 노동으로 인한 근골격계 질병률이 높은 것이 현실이다. 근골격계 질환을 유발시키는 원인 및 대처 방안을 여러 경로에서 찾을 수 있겠지만 농기구 디자인을 통한 사용성 개선이 이뤄진다면 농업 노동으로 인한 근골격계 질환을 줄일 수 있을 것이라 본다. 따라서 본 연구자는 농기구 디자인 연구를 통해 문제에 대한 해결 방안을 찾고자 했다. 연구방법 본 연구는 농업용 일륜차를 연구 대상으로 자세 부하를 줄일 수 있는 농기구 디자인을 제안하는 것을 연구 목표로 했다. 연구의 범위는 농자재 운반 작업을 하는 데 있어서 작업 중 발생하게 될 부하 요인을 현장연구를 통해서 발견하고 그것을 분석하여 도출된 데이터를 바탕으로 연구를 진행한 후 디자인을 제안했다. 연구결과 1차 사용자 중심의 연구와 2차 인간공학 중심의 연구를 통해서 도출된 자료를 바탕으로 연구를 진행한 후 핸들부, 바퀴부, 적재함, 색상, 형태, 재질 순으로 디자인을 제안해 보았다. 결론 이와 같은 디자인연구가 제품 적용 단계에서 예측과 다른 부하량 오류, 제작 기술의 한계, 디자인 요소들 간의 충돌 등 향후 풀어가야 할 문제가 있을 것이다. 하지만 신체 부하를 줄이기 위한 디자인연구가 농사용 일륜차에만 머무르지 않고 농기구 전반으로 확대된다면 농업 노동으로 인한 근골격계 질환을 줄이는데 기여할 수 있을 것이다. Background The development of modern scientific technology and the state/public-level realization of scientific farming have greatly achieved the improvement of agricultural productivity and reduction of manpower. However, due to many structural limitations such as aged farmers and sloped farmland, the musculoskeletal disease rate caused by agricultural labor is higher than any other industrial fields. Even though the causes for musculoskeletal diseases and coping measures could be found in many channels, it would be possible to reduce the musculoskeletal diseases by agricultural labor, by improving the usability through the design of farming tools. Thus, the researcher aims to seek for the solution measures through the research on the design of farming tools. Methods The purpose of this study is to suggest the design of farming tools that could reduce postural load, targeting the agricultural mono-wheeled barrow. In the range of this study, the researcher discovers the load factors that could occur in the middle of transporting agricultural materials through the field experiment, and then suggests the design by conducting a research based on the data of analysis. Result After conducting the study based on the data drawn through the first user-centered research and the second ergonomics-centered research, the researcher suggested the design in the order of handle part, wheel part, loading part, color, shape, and material. Conclusion In the design research like this, there would be problems that should be solved in the future such as load errors different from the prediction in the product application step, limitations of production technique, and conflicts between design elements. However, if the design research for reducing physical load is expanded to the overall farming tools without just staying in the agricultural mono-wheeled barrow, it could contribute to the reduction of musculoskeletal diseases caused by agricultural labor.